Antibacterial Activity of Indonesian Local Honey Against Strains of P. Aeruginosa, S. Aureus and MRSA - K. P., Ayu Diah; Sundoro, Ali; Sudjatmiko, Gentur (Jurnal Plastik Rekonstruksi, 2012)
Background: Honey has been used in wound care since ancient times. Many publications attest antibacterial activity of manuka honey against Pseudomonas aeruginosa, S. aureus, and Methicillin-resistant S. aureus (MRSA). However, antibacterial effect of local honey from Indonesia has never been studied and compared to medical grade honey before. This study aim to compare antibacterial activity of local honey and manuka honey against P. aeruginosa, S. aureus and MRSA.Methods: The honeys were tested for their antimicrobial activities with broth dilution method. Different concentrations of honey were prepared in reaction tubes. Strains of P.aeruginosa, S. aureus, and MRSA were grown in nutrient broth. These strains of bacteria then added to the different concentrations of honey. Minimum Inhibitory Concentrations (MIC) is the lowest concentration of the honey that yielded no growth of bacteria.Results: MIC of local honey for P. aeruginosa is 50%, for S. aureus is 100% and for MRSA is 100%. MIC of manuka honey for P. aeruginosa is 12,5%, for S. aureus is 25%, and for MRSA is 12,5%.Conclusion: Nusantara Manuka have the similar antibacterial activity spectrum against P. aeruginosa, MRSA and S. aureus, but it must be given in greater concentration to exert the same level of antibacterial activity with Manuka honey.